Quantitative Detection of Beef Contamination in Cooked Meat Products by ELISA. (23rd November 2019) - Thienes, Cortlandt P; Masiri, Jongkit; Benoit, Lora A; Barrios-Lopez, Brianda; Samuel, Santosh A; Krebs, Richard A; Cox, David P; Dobritsa, Anatoly P; Nadala, Cesar; Samadpour, Mansour
Abstract: Background: Concerns about the contamination of meat products with undeclared meats, and new regulations for the declaration of meat adulterants have established the need for a rapid test to detect beef adulteration to 0.1% sensitivity. Objective: To address this need, Microbiologique, Inc. has developed an ELISA that can quantify the presence of beef down to 0.1% (w/w) in cooked pork, horse, chicken, goat, and sheep meat. Results: The beef-authentication ELISA has an analytical sensitivity of 0.00022 and 0.00012% (w/v) for cooked and autoclaved beef, respectively, and an analytical range of quantitation of 0.025 to 2% (w/v), in the absence of other meats. Moreover, the assay is specific for cooked beef and does not cross react with common food matrixes. Conclusions: The assay is rapid, can be completed in 70 min, and can detect a 0.1% level of meat adulteration. The assay is an improvement over a previous U.S. Department of Agriculture's tested assay, which is sensitive to 1% adulteration and takes 2.5–3 h to complete. Highlights: The Microbiologique Cooked Beef ELISA can quantitate cooked beef in the presence of pork, horse, chicken, goat, and sheep meat to 0.1% (w/w) and is not affected by common food matrixes.